The Immune-Related Gene HCST as a Novel Biomarker for the Diagnosis and Prognosis of Clear Cell Renal Cell Carcinoma - Zhou, Yongying; Wang, Xiao; Zhang, Weibing; Liu, Huiyong; Liu, Daoquan; Chen, Ping; Xu, Deqiang; Liu, Jianmin; Li, Yan; Zeng, Guang; Li, Mingzhou; Wu, Zhonghua; et al. (Frontiers in Oncology, 2021)
Clear cell renal cell carcinoma (ccRCC) is the most common type of kidney tumor worldwide. Analysis of The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) databases showed that the immune-related gene (IRG) haematopoietic cell signal transducer (HCST) could provide guidance for the diagnosis, prognosis and treatment of CCRCC. The RNA-seq data of ccRCC tissues were extracted from two databases: TCGA (https://www.cancer.gov/about-nci/organization/ccg/research/structural-genomics/tcga) and GEO (https://www.ncbi.nlm.nih.gov/geo/). Corresponding clinical information was downloaded from TCGA. IRG data were extracted from the IMMPORT website (https://www.immport.org/). Differential analysis with R software (https://www.r-project.org/) was used to obtain a prognosis model of ccRCC IRGs. The differences were combined with the clinical data to assess the usefulness of HCST as a prognostic biomarker. Based on data obtained from the Oncomine (https://www.oncomine.org/), Human Protein Atlas (https://www.proteinatlas.org/) and PubMed (https://pubmed.ncbi.nlm.nih.gov/) databases, the expression levels of HCST in ccRCC, clinical-pathological indicators of relevance and influence on prognosis were analysed. Regulation of the HCST gene in ccRCC was assessed by gene set enrichment analysis (GSEA). In TCGA/GEO databases, the high HCST expression in tumor tissues was significantly correlated to the TMN stage, tumorr grade, invasion depth, and lymphatic metastasis (p < 0.05). The overall survival (OS) of patients with high HCST gene expression was significantly lower than that of patients with low HCST gene expression (p < 0.001). Multivariate Cox regression analysis suggested that HCST expression level (hazard ratio [HR] = 1.630, 95% confidence interval [CI] = 1.042–2.552), tumor cell grade (HR = 1.829, 95% CI = 1.115–3.001) and distant metastasis (HR = 2.634, 95%, CI = 1.562–4.442) were independent risk factors affecting the OS of ccRCC patients (all, p < 0.05). The GSEA study showed that there was significant enrichment in cell adhesion, tumorigenesis, immune and inflammatory responses in HCST high expression samples, . HCST expression was closely associated with the levels of infiltrating immune cells around ccRCC tissues, especially dendritic cells. In conclusions, present study suggested HCST was interrelated to the clinicopathology and poor prognosis of ccRCC. High HCST expression was also closely correlated with the levels of tumor-infiltrating immune cells, especially DCs.